Czytelnik i autorska metarefleksja w „Martwych duszach” Gogola - Kriwonos, Władisław (Studia Rossica Posnaniensia, 2012)
The article analyzes the functions and semantics of the term of the metatext “reader” playing an important role in metanarration in Gogol’s Dead Souls. The reader whom the author addresses is not only an imagined addressee, but also the imagined character of the author’s thinking who plays the role of the reader and stabilizes a possible relation to the written product. The author is discharged if the reader can mediate between the world of creativity and the world of heroes and can express a potentially possible opinion or judgement on the written product. Reproducing the reader’s reflection expressed in a certain form concerning a subject or imagen means the author, as a rule, foresees and anticipates that the reader will become acquainted with what is represented now, at the moment of creation, or in the prospective future.